Strengthening Midwives in the Traditional Healthcare Services Program (Yankestrad) in the Working Area of Ingin Jaya Public Health Center, Aceh Besar District - Yuniwati, Cut; Nurdahliana, Nurdahliana; Noviyanti, Noviyanti; Dewi, Ratna; Rimadeni, Yeni (Institute Of Computer Science (IOCS), 2024)
Program to Strengthen Midwives in Traditional Healthcare Services (Yankestrad) is an initiative aimed at enhancing the competence and capacity of midwives in providing traditional healthcare services. The program encompasses several key phases, including preparation, implementation, and evaluation. In the initial phase, 30 midwives underwent a refresher training program to ensure they were well-prepared for the subsequent comprehensive training. The program aimed to provide them with a deep understanding of traditional healthcare practices. The results of this community service program (Pengabdian Kepada Masyarakat) clearly indicate that the